Sognando la California. Italian translations of beat song lyrics - Kowalski, Piotr (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The article deals with song lyrics translation which was a common thing in Italy in the 1960s, the era of beat music. As a matter of fact, this new genre inspired by British and American groups such as The Beatles found fertile ground in the country which had just went through a period of prosperity which led to a rise of the middle class able to afford a growing number of luxury goods such as records. Many Italian performers preferred to copy foreign hits and remake them with Italian lyrics instead of composing new songs. The article deals with this phenomenon and proposes an analysis of three chosen song translations.